Kehamilan, Persalinan, Nifas Dan Tumbuh Kembang Anak Tetap Optimal Di Era Pandemi Covid-19: Pendampingan Masyarakat Dan Kader Posyandu - Alfi Muntafiah; Edy Priyanto; Qodri Santosa; Lily Burkon (Jurnal Pengabdian Pada Masyarakat, 2022)
Pandemic has had implications for all aspects of life in the world, including Indonesia. Under normal conditions, maternal and neonatal mortality is still a big challenge, especially during the current pandemic. Maternal and child health services are one of the services that are affected in terms of access and quality. The existence of restrictions on most routine services, including maternal and child health services, is feared to increase maternal and newborn morbidity and mortality, reduce maternal and child health, and interfere with child development. The team from FK UNSOED wants to take a role in the community to prevent an increase in infant and neonatal mortality in the midst of this pandemic situation. Through this activity, the community (especially pregnant women and mothers of toddlers) is expected to be able to strive for pregnancy, childbirth, postpartum, and child development so that they remain optimal. Activities are held through the lay webinar method and mentoring of posyandu cadres. The target audience for the public webinar is the general public and partners. The enthusiasm of the participants can be seen from the number of participants, who come from various circles and regions. The Zoom meeting was attended by 235 participants from various regions in Java and outside Java (Bali, Pontianak, etc.). Participants came from various backgrounds: 45.3% midwives, 15.4% housewives, 11.3% lecturers/teachers, 4.5% doctors, 2.4% posyandu cadres, private employees, students, etc. Meetings and direct mentoring activities in Karangnanas village were carried out with limited participants, namely representatives of posyandu cadres and village midwives. More intensive efforts are needed to empower cadres in the midst of this pandemic.